The Pedagogy of Physical Education, Sports, and Health Teachers in Using Google Classroom - David Loba; Isak Riwu Rohi; Paltiman Lumban Gaol; Yudith Febrianty Lerrick (MASI Mandiri Edukasi, 2026)
In the learning process, educators play a crucial role in motivating, guiding, and facilitating students’ achievement of intended learning outcomes. However, changing educational conditions and limitations on face-to-face instruction have required teachers to adapt to technology-based learning environments. In this context, Physical Education, Sports, and Health (PESH) teachers are expected to demonstrate strong pedagogical competencies, including the ability to design learning activities, implement effective instructional strategies, assess student learning outcomes, and integrate information and communication technology into their teaching. This study aimed to analyze the pedagogical practices of PESH teachers in utilizing Google Classroom as a learning platform. A descriptive research design was employed to provide an overview of teachers’ pedagogical competence in online learning settings. Data were collected using a structured questionnaire comprising 14 items on pedagogical competence. The data analysis process involved data reduction, data presentation, and data verification to ensure the accuracy and consistency of the findings. The results revealed that most PESH teachers strongly agreed with statements reflecting pedagogical competence in using Google Classroom. The overall level of agreement reached 81.20%, indicating a high level of pedagogical competence among PESH teachers in managing online learning. These findings suggest that Google Classroom can serve as an effective platform for supporting pedagogical practices and enhancing the quality of learning in Physical Education, Sports, and Health subjects, particularly in situations where conventional face-to-face instruction is limited.